Keputusan Panama Meratifikasi Konvensi Ballast Water Management - Prasetya, Muhammad Aji; Anggraini, Yayuk (Department of International Relations, Universitas Mulawarman, 2024)
This study aims to analyze and explain the factors that motivated Panama to ratify the Ballast Water Management Convention in 2016. The type of research is descriptive with the form of secondary data. The analysis technique that will be used is a qualitative technique. The theory used hereinafter uses the theory of National Interest and Foreign Policy by KJ Holsti. The results of this study indicate that the ratification of the Ballast Water Management convention by Panama in 2016 was based on national interests and also on its foreign policy through internal and external factors. The first of Panama's National Interests is to maintain Panama's aquatic environment, the second is to stabilize Panama's economy and increase employment, the third is to increase a positive image internationally, the fourth is to expand Panama's influence as a Flag State, Coastal State and Port State, and the fifth is to achieve Panama's SDG's vision and mission. And the factors that drive its foreign policy are internally such as geographical conditions, economic encouragement, to Panama's national attributes while externally such as Panama's position in the IMO, ballast water issues which are a regional and global problem to opinions from the international community.